Promosi Kesehatan Sendi Kuat Masa Tua Hebat di Puskesmas Karang Asam Kota Samarinda - Akhmad Jaizzur; Christina Emilia; Yolinda T andi Lino (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2026)
Joint pain is the most prevalent chronic health problem among the elderly and directly compromises quality of life. Low public knowledge of joint disease risk factors, prevention strategies, and self-management remains a critical barrier in primary healthcare settings. This study aimed to measure the effectiveness of an interactive health promotion session in improving elderly participants' knowledge of joint health. The activity was conducted on May 26, 2026 at Puskesmas Karang Asam, Samarinda, involving 25 participants. A pre-test and post-test design without a control group was applied. Educational media included PowerPoint presentations and informational leaflets. Knowledge was assessed using a 10-item true-or-false questionnaire. Results showed an increase in correct responses from 48% at pre-test to 79% at post-test, representing a 31-percentage-point gain. Based on Arikunto's (2006) classification, the post-test score falls within the "good" category (>75%). A single interactive health promotion session proved effective in raising elderly knowledge about joint health. Integration of physical practice such as joint exercise into future sessions is recommended to strengthen knowledge retention and support long-term behavioral change